Framework confinement of multi-metals within silica hollow spheres by one-pot synthesis process - Wenli Zhao; Yangfeng Liu; Ao Li; Fancang Meng; Yang Du; Qingmin Ji (Science and Technology of Advanced Materials, 2024)
The control incorporation of metals in silica hollow spheres (SHSs) may bring new functions to silica mesoporous structures for applications including catalysis, sensing, molecular delivery, adsorption filtration, and storage. However, the strategies for incorporating metals, whether through pre-loading in the hollow interior or post-encapsulation in the mesoporous shell, still face challenges in achieving quantitative doping of various metals and preventing metal aggregation or channel blockage during usage. In this study, we explored the doping of different metals into silica hollow spheres based on the dissolution-regrowth process of silica. The process may promote the formation of more structural defects and functional silanol groups, which could facilitate the fixation of metals in the silica networks. With this simple and efficient approach, we successfully achieved the integration of ten diverse metal species into silica hollow sphere (SHS). Various single-metal, dual-metal, triple-metal, and quadruple-metal doped SHSs have been prepared, with the doped metals being stable and homogeneously dispersed in the structure. Based on the structural characterizations, we analyzed the influence of metal types on the morphology features of SHSs. The synergistic effects of multi-metals on the catalysis applications were also studied and compared.